Thermal activation effect on palm oil clinker properties and their influence on strength development in cement mortar. (30th October 2016) - Karim, Mohammad Razaul; Hashim, Huzaifa; Abdul Razak, Hashim
Highlights: Thermal activation reduces the content of organic carbon in palm oil clinker powder. The percentage of inorganic oxides content increases in palm oil clinker through thermal activation process. Compressive strength is developed in thermally activated palm oil clinker powder blended cement mortar. Abstract: Compressive strength of mortar and concrete is an important consideration when incorporating waste as supplementary materials. Palm oil clinker (POC) is a waste material produced as result of incomplete burning of palm oil shells and mesocarp fibres as fuel to run steam turbines in palm oil mills. The current practice is to dump the waste in open land or landfill sites, which leads to environmental problems. Thermal activation was carried out to investigate the effects of applied heat energy on changes in chemical composition, physical properties, organic carbon content, morphology and crystalline structure of the mineral in palm oil clinker powder (POCP), and their influence on compressive strength development. The effects were investigated using TGA, XRF, TOC analyzer, SEM and XRD. Thermal activation was carried out in a programmable electrical furnace at 300 °C, 580 °C and 650 °C temperatures for 3 h. The right condition for thermal activation effect on POCP was found to be at 580 °C for 3 h, where the compressive strength of mortar was significantly increased.